Critical discourse Analysis of Torturing Male Prisoners in Abu Ghraib in The Independent's Political reports - Mustafa Rasheed; Imad Sameer (مجلة الآداب, 2023)
The present study under the title "Critical discourse Analysis of Torturing Male Prisoners in Abu Ghraib in The Independent's Political reports" is interested in revealing issues of power, dominance and ideologies in the political reports which talk about violence against men in Abu Ghraib. Revealing these issues in the report will be according to the use of CDA approach depending on the two scholars who are interested in this approach, Tuen Van Dijk, Norman Fairclough. In this study, there is a use of language as a tool to express dominance, power and ideology. With these linguistic elements, the previous issues are exploited indirectly by the American forces.